Sorption and Separation of Sugars with Adsorbents Based on Reversible Chemical Interaction - Johan A. Vente; Hans Bosch; André B. de Haan; Paul J.T. Bussmann (Adsorption Science & Technology)
The goal of this work was to enhance the selectivity of the separation of fructose or glucose from carbohydrate mixtures with adsorbents capable of reversible reaction. The experimental data presented demonstrate the feasibility of separating glucose from trans -galacto-oligosaccharides and fructose from fructo-oligosaccharides using resins as adsorbents. Comparison of the sorption properties of a resin functionalised with the bisulphite (HSO − 3 ) ion with its original chloride (Cl − ) form showed that the sorption of glucose increased due to interaction with the bisulphite group. In addition, functionalisation with bisulphite resulted in selectivity towards glucose relative to fructose and lactose. Moreover, chromatographic separation of glucose from trans -galacto-oligosaccharides on a bisulphite-loaded resin was improved compared to the same resin in the chloride form. However, the bisulphite unfortunately oxidised. Boronic acid-functionalised resin was selective towards fructose at pH 6.0 compared to glucose, indicating complex formation between fructose and boronic acid. Although complex formation with boronate has been assumed to be even stronger than with boronic acid, increasing the pH to a value above the pK a of the functional group did not improve fructose sorption. Chromatographic separation of fructose from fructo-oligosaccharides was obtained on boronic acid-functionalised resin as a result of complex formation with fructose. These results show that reversible chemical reactions can lead to an improvement in the performance of adsorbents for sugar separations.